Silurian to Early Devonian organic-walled phytoplankton and miospores from Argentina: Biostratigraphy and diversity trends - Rubinstein, Claudia Viviana (2011)
The distribution and diversity of marine palynomorphs, such as acritarchs and chlorophytes, and terrestrial palynomorphs, such as miospores, are controlled mainly by palaeoenvironmental and palaeogeographical conditions. Recently, global patterns of organic-walled phytoplankton were illustrated for the Late Silurian to earliest Devonian based on data from different stratigraphic sections and palaeocontinents. Here, we analyze the Silurian and the Early Devonian diversity in the Argentinean Precordillera, Central Andean, and Chacoparanense basins. The evolution of the diversity is evaluated in a well-constrained biostratigraphic framework, bearing in mind local palaeoenvironmental conditions and changes within each basin. Taking into account recently published and unpublished data from well-dated sections, the biodiversity of Silurian phytoplankton seemingly increases upwards, reaching its maximum peak during the Ludlovian. However, palynomorphs are rarely recorded in Wenlockian strata, and the supposed Pridolian layers are not confidently well constrained. The first record of trilete spores in Argentina is Ludlovian, approximately 30 million years after their first appearance in the Late Ordovician. Palynomorph diversity increases in the Early Devonian, with a higher diversity of miospores than that of the marine phytoplankton. We interpret possible discrepancies in biodiversity trends of organic-walled phytoplankton between Argentina and other regions, as related to the quantitatively and qualitatively disparity of data, as well as the lack of rigorous biostratigraphic and palaeoenvironmental assessments of the Argentinean basins.